The biogeography of Gabonese savannas: Evidence from termite community richness and composition - Fidèle Evouna Ondo; Kathryn J. Jeffery; Robin Whytock; Katharine A. Abernethy; Pierre Couteron; Paul Eggleton; Claire Griffin; Nicolas J. Ostle; Aurelie‐Flore Koumba Pambo; Alfred Ngomanda; Josué Edzang Ndong; Catherine L. Parr (Journal of Biogeography, 2023)
Aim The mosaic of savannas that persists in the forest‐dominant Congo Basin is thought to be palaeoclimatic relics, but past biogeographical processes that have formed and maintained these systems are poorly understood. Here, we explored the post‐Pleistocene biogeography of Gabon's savannas using termites as biological indicators to understand historical and mechanistic factors influencing present‐day termite communities in the country's extant savannas. Location Gabon, Central Africa. Taxon Blattodea: Termitoidae. Methods Using standardised transect methods, we sampled termite communities in four disjunct modern savanna areas of Gabon: the centre (Lopé), the southeast (Batéké) and the south (Mayombe North and South). Termites at Lopé were collected in three habitats (annually burned savannas, savannas with a depressed fire regime and forest). We used DNA barcoding of the COII region to identify termite species and compared abundance, species richness and community composition across areas and habitats. Results Community composition differed greatly between Lopé and both Batéké and Mayombe savannas with Lopé being exceptionally depauperate and lacking characteristic savanna species. Within Lopé, termite abundance and diversity was highest in forests and lowest in annually burned savannas, with a gradual change in species composition across the forest–savanna gradient associated with fire history. Main Conclusions The absence of savanna typical species in Lopé savannas challenges current assumptions that these savannas were linked to the south/southeastern savannas during the Pleistocene and suggests a different evolutionary history. Lopé savannas may instead have opened as an isolated grassland and never have been contiguous with neighbouring savannas, or were isolated soon after forest expansion began and have now lost savanna‐typical species. Furthermore, the patterns of termite community composition in fire suppressed savannas support a hypothesis of rapid change driven by fire frequency where either fire suppression or infrequent burning over 23 years has meant savannas have become ecologically much more forest‐like.

Invasion legacy effects versus sediment deposition as drivers of riparian vegetation - Zarah Pattison; Robin Whytock; Nigel Willby (Biological Invasions, 2018)

Bird‐community responses to habitat creation in a long‐term, large‐scale natural experiment - Robin C. Whytock; Elisa Fuentes‐Montemayor; Kevin Watts; Patanjaly Barbosa De Andrade; Rory T. Whytock; Paul French; Nicholas A. Macgregor; Kirsty J. Park (Conservation Biology, 2018)
Ecosystem function and resilience are compromised when habitats become fragmented due to land‐use change. This has led to national and international conservation strategies aimed at restoring habitat extent and improving functional connectivity (i.e., maintaining dispersal processes). However, biodiversity responses to landscape‐scale habitat creation and the relative importance of spatial and temporal scales are poorly understood, and there is disagreement over which conservation strategies should be prioritized. We used 160 years of historic post‐agricultural woodland creation as a natural experiment to evaluate biodiversity responses to habitat creation in a landscape context. Birds were surveyed in 101 secondary, broadleaf woodlands aged 10–160 years with ≥80% canopy cover and in landscapes with 0‐17% broadleaf woodland cover within 3000 m. We used piecewise structural equation modeling to examine the direct and indirect relationships between bird abundance and diversity, ecological continuity, patch characteristics, and landscape structure and quantified the relative conservation value of local and landscape scales for bird communities. Ecological continuity indirectly affected overall bird abundance and species richness through its effects on stand structure, but had a weaker influence (effect size near 0) on the abundance and diversity of species most closely associated with woodland habitats. This was probably because woodlands were rapidly colonized by woodland generalists in ≤10 years (minimum patch age) but were on average too young (median 50 years) to be colonized by woodland specialists. Local patch characteristics were relatively more important than landscape characteristics for bird communities. Based on our results, biodiversity responses to habitat creation depended on local‐ and landscape‐scale factors that interacted across time and space. We suggest that there is a need for further studies that focus on habitat creation in a landscape context and that knowledge gained from studies of habitat fragmentation and loss should be used to inform habitat creation with caution because the outcomes are not necessarily reciprocal.